Transformasi Pembelajaran Pendidikan Agama Kristen Berbasis Teologi pada Era Society 5.0 - Yorhans Yupiter Nau; Daud Saleh Luji; I Made Suardana (Indo Publishing, 2026)
The rapid development of digital technology in the Society 5.0 era requires educational transformation that integrates technological innovation with the strengthening of human values and spirituality. In the context of Christian Religious Education (CRE), such transformation is not merely oriented toward the utilization of digital technology but also toward reinforcing theological foundations as the basis for nurturing students' faith and Christ-like character. This study aims to analyze theology-based transformation in Christian Religious Education learning in the Society 5.0 era, identify the challenges of its implementation, and formulate a conceptual learning model that integrates biblical theology with digital pedagogy. This research employed a qualitative approach using a library research method. The data were collected from reputable Indonesian journal articles, theology books, Christian Religious Education references, and other scientific publications published between 2016 and 2026. Data were analyzed through content analysis involving data reduction, categorization, interpretation, and synthesis. The findings reveal that the transformation of Christian Religious Education learning in the Society 5.0 era should be carried out through a paradigm shift from teacher-centered learning to student-centered learning by integrating digital technology, transformative pedagogy, digital literacy, and biblical theology. However, its implementation continues to face several challenges, including limited teachers' digital competence, unequal technological infrastructure, insufficiently adaptive curricula, and the challenge of maintaining theological identity amid rapid digital advancement. This study proposes a conceptual model of theology-based Christian Religious Education transformation consisting of four main pillars: biblical theology, transformative pedagogy, digital technology integration, and Christ-centered character formation. This model is expected to serve as a practical reference for teachers in designing innovative, contextual, humanistic, and Christ-centered learning in the Society 5.0 era.